Unambiguous identification of α-Gal epitopes in intact monoclonal antibodies by NMR spectroscopy. Issue 1 (31st December 2022) - Hinterholzer, Arthur; Moises, Jennifer; Regl, Christof; Schwap, Sebastian; Rapp, Erdmann; Huber, Christian G.; Schubert, Mario
ABSTRACT: The α-Gal epitope consisting of the terminal trisaccharide Galα1, 3Galβ1, 4GlcNAc exposed on cell or protein surfaces can cause severe immune reactions, such as hypersensitivity reactions, in humans. This epitope is also called the xenotransplantation epitope because it is one of the main reasons for the rejection of non-human organ transplants by the human innate immune response. Recombinant therapeutic proteins expressed in murine cell lines may contain α-Gal epitopes, and therefore their absence or presence needs to be tightly monitored to minimize any undesired adverse effects. The analytical identification of α-Gal epitopes in glycoproteins using the common standard techniques based on liquid chromatography and mass spectrometry is challenging, mainly due to the isobaricity of hexose stereoisomers. Here, we present a straightforward NMR approach to detect the presence of α-Gal in biotherapeutics based on a quick screen with sensitive 1 H- 1 H TOCSY spectra followed by a confirmation using 1 H- 13 C HSQC spectra. Abbreviations : α-Gal: α1, 3-linked galactose; AGC: automatic gain control; CHO: Chinese hamster ovary; CE: capillary electrophoreses coupled to mass spectrometry; COSY: correlation spectroscopy; DSS: 2, 2-dimethyl-2-silapentane-5-sulfonate; DTT: dithiothreitol; GlcNAc: N-acetyl glusomamine; HCD: higher-energy collisional dissociation; HMBC: heteronuclear multiple-bond correlation; HPLC: high-performance liquid chromatography; HSQC: heteronuclear single-quantum corre; LacNAc: N-acetyl lactosamine; mAb: monoclonal antibody; MS: mass spectrometry; NMR: nuclear magnetic resonance; NOESY: 2D) nuclear Overhauser spectroscopy; PEG: polyethylenglycol; pH*: observed pH meter reading without correction for isotope effects; PTM: post-translational modification; TCEP: tris(2-carboxyethyl) phosphine hydrochloride; TOCSY: total correlation spectroscopy; xCGE-LIF: multiplex capillary gel electrophoresis with laser-induced fluorescence detection.